Mitochondria, Estrogen and Female Brain Aging - Lejri, Imane; Grimm, Amandine; Eckert, Anne (Frontiers in Aging Neuroscience, 2018)
Mitochondria play an essential initial role in the generation of steroid hormones including the female sex hormones. These hormones are, in turn, able to modulate mitochondrial activities. Mitochondrial impairment is one of the central features of aging due to the crucial roles of mitochondria in cell maintenance, survival and wellbeing, because they are the main source of energy as well as of reactive oxygen species (ROS) within the cell. In women’s health, estrogen, especially estradiol (E2) the major estrogen in most mammals, including women, plays an important role during adulthood not only in the estrous cycle, but also in the brain via neuroprotective, neurotrophic and antioxidant modes of action. The hypoestrogenic state in the peri- as well as prolonged post-menopause might increase the vulnerability of elderly women to brain degeneration and age-related pathologies. However, the underlying mechanisms that affect these processes are not well elucidated. Understanding the relationship between estrogen and mitochondria might therefore provide better insights into the female aging process. Thus, in this review, we firstly describe mitochondrial dysfunction in the aging brain. Secondly, we discuss the estrogen-dependent actions on the mitochondrial activity and their potential implications during female aging.